The Adjacency Pairs in the Bing Bunny Animated Series - Euis Kurniasih; Dwinesa Anggraini (Surakarta English and Literature Journal, 2023)
An animated series narrated about a preschool bunny named Bing shows how he interacts with the world around him with the support of his caretaker through little everyday experiences. The goal of this study is to explore the pattern of adjacency pairs among Bing and his friends with their caregivers in the Bing Bunny animated series. This study applied qualitative methods and conversational analysis. The data was gathered from the conversation of all characters in Bing Bunny's official channel on YouTube. The result shows that adjacency pairs in five episodes of the Bing Bunny animated series consist of 10 types. They are greeting-greeting, summon-answer, question-answer, requestacceptance, request-refusal, offer-accept, blame-denial, apology-minimization, assertionagreement, announcement-acknowledgement. The adjacency pair patterns reveal the successful engagement among the children and the caregivers. The exposure of adjacency pairs to children will contribute to language acquisition, cognitive development, social understanding, and overall learning.